Understanding the Potentials of Narrowband Internet of Things (NB-IoT) Cellular Technology: Salient Features, Architecture, Smart Applications and Quality of Service (QoS) Challenges - Muhammad Waseem; Alicia Lopez; Pedro Luis Carro; Maria Angeles Losada; Dwight Richards; Abdul Aziz (IEEE Open Journal of the Communications Society)
Since the last decade, the number of Internet of Things (IoT) devices has increased dramatically and to operate them at low power has been a great challenge. Therefore, significant efforts have been made by the researchers to innovate such technologies that may operate the IoT devices at low power. In this context, several Low Power Wide Area Network (LPWAN) technologies have been introduced which have revolutionized the world of IoT. Narrowband Internet of Things (NB-IoT) is one of the protocols that was developed by 3rd Generation Partnership Project (3GPP) in June 2016 to cater the stringent requirements of IoT devices. In this paper, a comprehensive analysis on the features, architecture, signals and channels of NB-IoT is provided. Additionally, a detailed description of the applications of NB-IoT is also presented. Finally, some crucial challenges related to the quality of service (QoS) of NB-IoT are highlighted in this paper.